Role of hydration forces in the properties of electrolyte solutions in the bulk and at interfaces. Issue 1753 (11th February 2015) - Sushko, Maria L.; Rosso, Kevin M.
ABSTRACT: We present a theoretical approach for modeling electrolyte solutions at interfaces that reaches into the mesoscale while retaining molecular detail. The total Hamiltonian of the system includes interactions arising from density and charge density (ion correlation) fluctuations, direct Coulomb interactions between ions, and at interfaces the image interactions, ion-solid and ion-water dispersion interactions. The model was validated against its ability to reproduce ion activity in 1:1 and 2:1 electrolyte solutions in the 0-2 M concentration range, its ability to capture the ion-specific effect in 1:1 electrolytes at the air-water interface, and solvent structure in a confined environment between hydrophobic surfaces, revealing the central role of ion hydration interactions in specific ion thermodynamic properties in the bulk solutions and at interfaces. The model is readily extensible to treat electrolyte interactions and forces across charged solid-water interfaces.